Strategies for Handling the Poor Culture of Slum Communities, in Kenjeran Sub-district, Surabaya City - Tjahyanityasa, Wanda Fitri; Marwasta, Djaka; Harini, Rika (Journal of Geosciences and Environmental Studies, 2025)
Land use in the North Surabaya City area can still be found in the presence of slums, one of the sub-districts where this phenomenon occurs is in the Kenjeran District. Migration that continues to increase significantly can cause various problems in a residential area. This research aims to formulate a strategy for handling the distribution of slums based on poor culture in the Kenjeran Sub-district. Javanese and Madurese ethnic communities inhabit the majority of the Kenjeran Sub-district. The research used a descriptive qualitative method with SWOT analysis to handle the poor cultural characteristics of slum communities. Data collection from respondents through observation, questionnaires, interviews, and documentation. The unit of analysis in this research is a grouping of people in slums. The population in this study was 7,208 poor people in the Kenjeran Subdistrict. Still, in this study there were 99 respondents consisting of five community groupings, namely fishermen clusters with poor cultural traits of resignation to fate, apathy, dependence, and kinship traits, fishmonger clusters with poor cultural traits of apathy, dependence and kinship traits, culinary clusters with poor cultural traits of apathy and dependence traits, clusters with poor cultural traits of apathy and dependence traits, clusters with poor cultural traits of apathy, and clusters with poor cultural traits of kinship. Artisans with poor cultural traits of resignation to fate and dependency, and tourist attraction clusters with poor cultural traits of dependency.